Synthesis of Aqueous Polymer Isocyanate for Plywood Adhesive - Euis Hermiati; Dede Heri Yuli Yanto; Faizatul Falah (Jurnal Ilmu dan Teknologi Kayu Tropis, 2009)
The aim of this research was to produce natural rubber-based Aqueous Polymer Isocyanate (API) adhesives that could meet standard for exterior grade plywood adhesive.  Base polymers used were Natural Rubber Latex (NRL), Natural Rubber Latex - Styrene (NRL-St), and polyvinyl alcohol (PVOH).There were two kinds of adhesives produced; one was using NRL and PVOH as base polymers, and the other one was using NRL-St and PVOH as base polymers.  Isocyanate crosslinking agent was added to each kind of adhesives at 2.5; 5; 10; 15 and 20% of the weight of the base polymers.  They were measured for their total solid content (gravimetric method), pH (using pH meter), specific gravity (using picnometer) and viscosity (using Brookfield viscometer). Thermal analyses using TG/DTA was conducted at the addition of 0, 5 and 15% cross-linking agent. The adhesives were spread on the surface of Red Meranti  (Shorea sp.) veneers (250 x 250 x 2.1 mm core; 250 x 250 x 1.5 mm face and back) at the glue spread rate 400 g/m2 DGL (double glue line). The veneers with adhesives were cold pressed at 10 kg/cm2 for 10 minutes and then hot pressed at 10 kg/cm2, 110ºC for 5 minutes.  The plywood produced was conditioned for 2 weeks, then they were measured for their bond strength, delamintaion ratio, water absorption, and thickness swelling. Results of this study showed that either NRL or NRL-St could be used as one of base polymers in preparing API adhesive.  Bond strength of plywood adhered with API adhesives made of NRL-St at all levels of isocyanate crosslinking agent addition were higher than those made from NRL. The addition of 10% or more isocyanate croslinkers to NRL/PVOH (50:50) or to NRL-St/PVOH (50:50) could produce plywood having bond strength that could meet interior grade standard.  Plywood having bond strength of exterior grade standard were produced when 15% or more isocyanate crosslinkers were added to NRL-St/PVOH (50:50) or when 20% or more isocyanate crosslinkers were added NRL/PVOH (50:50).